Distance Learning Experience: Unleashing the Power of Peardeck for Post-Pandemic Education - Roqobih, Fikky Dian; Astriani, Dyah (Jurnal Pijar Mipa, 2024)
Pear Deck is one of the tools for presenting web-based online slides. This research was implemented on 26 preservice science teachers who have heterogeneous thinking skills. This research examined the improvement of preservice science teachers’ learning outcomes through interactive online learning using Pear Deck after the pandemic era. The instruments used were written tests that were given twice before and after learning. This research was a pre-experimental design including pre-test and post-test design. Data earned was then analysed using an N-gain score and paired t-test but normality and homogeneity test was conducted before it. Data is said to be normally distributed if the Lcount < Ltab, and is said to be homogeneous if the Fcount < Ftab. There was a significant difference between learning outcomes before and after treatment if tcount < ttab. with α = 0,05. Learning with Pear Deck increases the average preservice science teacher’s score. the data were normally distributed, and then a homogeneity test was conducted with the result Fcount = 1,204 and Ftable = 1,955. Which means that Fcount < Ftable. The data were stated as homogenous. Pear Deck has a significant effect on the improvement of preservice science teacher’s learning outcomes. This is proven by the majority of students having high N-gain scores through their improvement on their test before (pretest) and after (posttest) learning. 77,78% of preservice science teacher also belonged to moderate-high increases in their scores. Results of the T-test concluded that tcount=23,10>ttable=2,06 means that H0 was rejected. So, the use of Pear Deck in distance learning had a significant effect on improving preservice science teacher’s learning outcomes.